2009
DOI: 10.1152/japplphysiol.91054.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen stimulates vasculogenic stem cell growth and differentiation in vivo

Abstract: ϩ SPCs were identified. HBO2 and lactate accelerated channel development, cell differentiation based on surface marker expression, and cell cycle entry. CD34ϩ SPCs exhibited increases in thioredoxin-1 (Trx1), Trx reductase, hypoxia-inducible factors (HIF)-1, -2, and -3, phosphorylated mitogen-activated protein kinases, vascular endothelial growth factor, and stromal cell-derived factor-1. Cell recruitment to Matrigel and protein synthesis responses were abrogated by N-acetyl cysteine, dithioerythritol, oxamate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 70 publications
5
94
0
Order By: Relevance
“…Under physiological conditions, the generation of ROS is relatively lower in BM-derived stem cells compared to cycling cells, which potentially could reduce the frequency of DNA damage (Arai et al, 2004;Kiel et al, 2007;Yoshihara et al, 2007). However, in pathophysiological states, such as hypertension, cell differentiation and proliferation may increase the level of ROS in BM causing DNA damage (Sattler et al, 1999;Milovanova et al, 2009;Tesio et al, 2011). Accordingly, we recently demonstrated that intracellular-generated ROS can lead to DNA damage in mononuclear cells of 2K1C hypertensive mice .…”
mentioning
confidence: 99%
“…Under physiological conditions, the generation of ROS is relatively lower in BM-derived stem cells compared to cycling cells, which potentially could reduce the frequency of DNA damage (Arai et al, 2004;Kiel et al, 2007;Yoshihara et al, 2007). However, in pathophysiological states, such as hypertension, cell differentiation and proliferation may increase the level of ROS in BM causing DNA damage (Sattler et al, 1999;Milovanova et al, 2009;Tesio et al, 2011). Accordingly, we recently demonstrated that intracellular-generated ROS can lead to DNA damage in mononuclear cells of 2K1C hypertensive mice .…”
mentioning
confidence: 99%
“…Recent publications have reported variable outcomes in great part because of using protocols that differ significantly in depth, duration, frequency and number of sessions [36][37][38]. It appears that HBOT can be effective in decreasing chronic inflammation in the brain by reducing pro-inflammatory cytokine activation and through provocation of stem cell activity [7][8][9][10]. The repeat brain SPECT indicated the valuable contribution of this technique as a functional imaging biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The treatments included 1) hyperbaric oxygen therapy (HBOT), 2) combination therapy of infused ketamine concurrent with transcranial magnetic stimulation (TMS), 3) injections of perispinal etanercept (PSE), and 4) non-invasive trans-nasal Sphenopalatine Ganglion (SPG) block. HBOT is believed to have anti-inflammatory effects, reducing the excess of proinflammatory cytokine activation such as TNF-alpha and facilitating improvement by provocation of stem cell activity [7][8][9][10]. The combination therapy of infused ketamine administered concurrent to TMS appears to address the abnormalities in brain circuits found both in treatment resistant depression and treatment resistant central pain [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism underlying HIF-2α expression in cancer requires further study (Milovanova et al, 2009). The widespread occurrence of up-regulation of HIF-2α in common cancers and the involvement of hypoxia pathways in tumor angiogenesis indicate its importance and wide applicability.…”
Section: Discussionmentioning
confidence: 99%